Ready, set, …rollout? – The role of heterogeneous actors and proximities in the delayed smart meter rollout in Germany - Sabrina Paustian; Julia Köhlke; Jannika Mattes; Sebastian Lehnhoff (Cleaner Engineering and Technology)
Current technological developments for the energy transition are becoming increasingly digitalised as they integrate Information and Communication Technologies (ICT). Nonetheless, we know little about how these digitalisation processes occur. This paper aims to understand the role of heterogeneous actors in a specific digitalisation process, namely the rollout of smart meters in Germany. Smart meters are widely considered as a key technology to both the digitalisation of the energy sector and a further acceleration of the energy transition. As the smart meter rollout in Germany did not occur smoothly, we argue that there is more to that than technological and legal aspects. Instead, the involved actors such as producers, public authorities and distribution system operators (DSO) with diverse knowledge and interests are key to understanding the implementation inefficiencies, i.e.in this case: a significant delay. To disentangle these challenges, we draw on Boschma (2005) proximity model. It offers a multi-faceted view of actor heterogeneity by considering five different aspects: cognitive, organisational, institutional, social and geographical proximities. Our case study with expert interviews reveals multiple reasons for the delay, including knowledge boundaries, new business models or working practices. Disentangling these, the paper shows the importance of actor constellations in digitalisation processes in the energy transition and thereby contributes to the debate on the interrelatedness of digitalisation and transitions.